Product Innovation Strategy in Increasing the Competitiveness of the Creative Bamboo Weaving Industry in Ringinagung Village, Magetan (UD. Putri Ragil) - Rima Dwi Novianawati; Irma Yuliani (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
The development of technology has increased consumer expectations of product diversity and quality, thus encouraging creative industry players to constantly innovate. One of the creative industries in Magetan Regency is the woven bamboo industry (Industri Anyaman Bambu). This industry is able to maintain competition through product innovation by preserving local culture and contributing to economic growth. This study aims to analyze the implementation of product innovation strategies, challenges, and impacts on the competitiveness of the creative industry. Data were obtained through interviews and observations and analyzed using descriptive analysis. This research engaged business owners, employees, and consumers of woven bamboo as key informants. The results showed that there are four main innovation strategies employed by the Woven Bamboo Industry, including enhancing the quality of products, diversifying designs, strengthening brands image, and optimizing social media for marketing. Meanwhile, the main obstacles include limited human resources, production constraints during the rainy season, and lack of support from the local government. The significant impacts derived from the innovation strategy are increasing sales, expanding market reach, and increasing business competitiveness. In addition, this innovation also encourages improved employee skills and increased consumer desirability. Perkembangan teknologi telah meningkatkan ekspektasi konsumen terhadap keragaman dan kualitas produk, sehingga mendorong pelaku industri kreatif untuk terus berinovasi. Salah satu industri kreatif di Kabupaten Magetan adalah industri anyaman bambu. Industri ini mampu mempertahankan persaingan melalui inovasi produk dengan melestarikan budaya lokal dan berkontribusi terhadap pertumbuhan ekonomi. Penelitian ini bertujuan untuk menganalisis penerapan strategi inovasi produk, tantangan, dan dampaknya terhadap daya saing industri kreatif. Data diperoleh melalui wawancara dan observasi serta dianalisis menggunakan analisis deskriptif. Penelitian ini melibatkan pemilik usaha, karyawan, dan konsumen anyaman bambu sebagai informan kunci. Hasil penelitian menunjukkan bahwa terdapat empat strategi inovasi utama yang diterapkan oleh Industri Anyaman Bambu, yaitu peningkatan kualitas produk, diversifikasi desain, penguatan citra merek, dan optimalisasi media sosial untuk pemasaran. Sementara itu, kendala utama yang dihadapi antara lain keterbatasan sumber daya manusia, kendala produksi saat musim hujan, dan kurangnya dukungan dari pemerintah daerah. Dampak signifikan yang diperoleh dari strategi inovasi tersebut adalah peningkatan penjualan, perluasan jangkauan pasar, dan peningkatan daya saing usaha. Selain itu, inovasi ini juga mendorong peningkatan keterampilan karyawan dan peningkatan daya tarik konsumen.